(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores Uzbek-English language dynamics through artificial intelligence. It separates historical backgrounds, syntactic structures, semantic maps, and translation barriers. Through AI, it provides insight into addressing linguistic gaps, demonstrating the potential of technology in improving intercultural communication and understanding.